Strategi Gatra Sumbagsel Dalam Mempertahankan Eksistensi Media Informasi Di Era New Media - Yulmi Pransiska; Sumaina Duku; Hasril Atieq Pohan (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This study aims to find out how the Gatra Sumbagsel Strategy maintains the existence of information media in the new media era. With the presence of Gatra Sumbagsel media as an extension of Gatra Nasional in maximizing business potential in Sumbagsel which has not been optimally exploited by Gatra Nasional. This type of research uses descriptive qualitative methods with primary data sources from interviews and secondary data sources from observation and documentation. The data collection carried out by the researcher was in three stages: data reduction, data presentation, and drawing conclusions. The results of the study show the strategies implemented by Gatra Sumbagsel in maintaining its existence as an information medium: Conduct strategic management, analyze the environment, formulate strategies, implement and then evaluate. the program carries out program planning, utilizes social media as a medium in promoting its programs or providing information, implementing strategies in production, monitoring and evaluating programs, implementing strategies in HR development of gatra sumbagsel providing opportunities for employees of gatra sumbagsel to contribute ideas and provide training to employees of gatra sumbagsel. Based on the results of the research conducted by the researchers, it can be concluded how the South Sumatra gatra strategy maintains the existence of information media in the new media era. After managing the Gatra Sumbagsel media strategy, it can maintain the existence of information media in the new media era, because it has contributed to and has followed technological developments where social media has become a medium with a dual role, the responsibility of the elite to a quality public. Media Gatra Sumbagsel is expected to continue to innovate in making quality programs and in accordance with the wishes of the community. As well as improve the quality of the program.